The clinical and cost effectiveness of surgical repair of partial rotator cuff tears in patients with subacromial shoulder pain: a comparison of surgical repair versus surgery with no repair. Partial Rotator Cuff Repair Trial (PRoCuRe Trial) - Rees, J; Carr, A; Cook, J; Rangan, A; Millar, J; van der Windt, D; Keele, A; Prieto-Alhambra, D; Pinedo-Villanueva, R; Jaggi, A; Cooper, C; Jepson, M; et al. (F1000Research, 2023)
Aims and objectives: To assess if surgical repair of partial rotator cuff tears is effective in patients with persistent shoulder pain despite physiotherapy and steroid injection.